Peran Virgin Coconut Oil (VCO) terhadap Derajat Medical Adhesive-Related Skin Injury (MARSI) pada Bayi Prematur saat Pelepasan Plester Orogastric Tube: The Role of Virgin Coconut Oil (VCO) in the Degree of Medical Adhesive-Related Skin Injury (MARSI) among Preterm Infants during Orogastric Tube Tape Removal - Khairun Nisa; Hari Ghanesia Istiani; Nur Eni Lestari (Journal of Nursing Education and Practice, 2025)
Introduction: Medical Adhesive Related Skin Injury (MARSI) is a skin injury caused by the use of medical tape, which often occurs in premature infants during the removal of Orogastric Tube (OGT) tape because the skin is very susceptible to injury. Virgin Coconut Oil (VCO) has emollient and anti-inflammatory properties that can protect skin integrity. Objectives: The purpose of this study was to determine the effect of removing OGT tape using VCO on the degree of MARSI in premature infants. Method: The study design used a quasi-experimental posttest-only design with a control group. The average monthly population of infants was 30. The study sample consisted of 30 premature infants, divided into an intervention group and a control group. The sampling technique used was purposive sampling. The instruments used were the Standard Operating Procedure for removing OGT tape using VCO and the MARSI degree observation sheet. The bivariate test used the Mann-Whitney test. Result: The results showed a p-value = 0.001 (p <0.05), indicating a significant difference between the two groups. Conclusion: The use of VCO has been proven effective as a preventive intervention to reduce the degree of MARSI in premature infants during OGT tape removal. This can be recommended for hospitals as one of the Standard Operating Procedures.